Pengaruh Self-Esteem dan Regulasi Emosi Terhadap Tendensi Koping FFFFs Dewasa Awal Stres Tinggi di Makassar - M, Nurul Auralia; Widyastuti, Widyastuti; Cahyaningrum, Kartika (Universitas Muhammadiyah Metro, 2026)
Early adulthood (ages 18–40) is a period vulnerable to high stress and quarter-life crisis, with the prevalence of emotional mental disorders in Makassar reaching 17.86% (higher than the national average of 9.8%). This study aims to examine the influence of self-esteem and emotion regulation on the tendency of 4F coping mechanisms (fight, flight, freeze, fawn) in early adults with high stress in Makassar City. Using a quantitative approach with a multinomial logistic regression design, the study involved 229 early adult respondents aged 18–40 years who had high stress levels based on the Perceived Stress Scale (PSS). Research instruments consisted of the Rosenberg Self-Esteem Scale, the Emotion Regulation Questionnaire (ERQ), and the Fight-Flight-Freeze-Fawn Test. Results showed the majority of respondents had moderate self-esteem (40.2%) and moderate emotion regulation (49.3%), with the freeze coping tendency being most dominant (41.9%). Regression analysis revealed emotion regulation had a significant influence on the 4F coping mechanism (p=0.001), while self-esteem was not significant (p=0.648). The combined contribution of both variables was 52.9% (R²=0.529), leaving 47.1% influenced by factors outside the model. The study concludes that emotion regulation ability is a critical factor in determining the tendency towards 4F coping mechanisms in this population, while self-esteem did not show a direct influence. These findings confirm the importance of interventions focused on strengthening emotion regulation to reduce maladaptive responses to high stress in early adults within urban contexts like Makassar